To solve the equation based on the statement: "The difference of six times a number and seven results in 35", we can set up the equation as follows:
Let the unknown number be represented by \( x \).
The equation can be expressed as: \[ 6x - 7 = 35 \]
Now, to solve for \( x \), we need to isolate the variable. The steps to do this would be:
-
Add 7 to both sides of the equation to eliminate the -7 on the left side: \[ 6x - 7 + 7 = 35 + 7 \] \[ 6x = 42 \]
-
Then divide both sides by 6 to solve for \( x \): \[ x = \frac{42}{6} \] \[ x = 7 \]
Thus, the correct steps to solve the equation are:
- Add 7, and then divide by 6.
So the answer is: Add 7, and then divide by 6.